Test and assessment for improvement of the endurance in youth soccer - D'Isanto, T. (Journal of Human Sport & Exercise, 2020)
The aim of the study was to analyse and estimate how much is the improvement of the performance, on two groups of 15 male among 13-14 years. The group A continue with the trainings during summer period, while the group B does not continue the trainings. The study method is experimental. Data were collected during eight weeks (during summer period). All data detected were expressed as average ± SD on: height, weight, body mass index (BMI) and Cooper Test. The statistical analysis of the data foresees the use Student T-test for estimate the performance in the two groups in the summer period and between the two groups. The significant differences has been fixed in p < .05. The tests that have been made to the male young soccer players, are easy to administer and are intended to investigate two different characteristics of the endurance (general and specific). The results show that there is a significant difference between the two groups in September. For the group B (that do not continue the training during the summer period) there is not a significant difference; while for the group A (that continue the training during summer period) there is a significant difference. These analyse and evaluate of improvement of the performance allow at the coaches of monitor the training process and to design the training load.